POTRET KESESATAN DAN KESADARAN AKIBAT CINTA TERHADAP BUDAYA BARAT DALAM CERPEN â€œSETINGGI-TINGGI TERBANG BANGAUâ€ KARYA ANJAR ASMARA - Fitrah, Yundi (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
A short story entitled â€œSetinggi-tinggi Terbang Bangauâ€ written by Anjar Asmara is one of short stories that was writtin in Japanese colonialization in Indonesia. In this short story, the writer figures disgression that was caused by love of western culture. By using structural-instrinsic writing approach, it can be seen from the characters who behave like. Westerners, follow netherland life style and leave behind Indonesian culture. Keywords: Implementation of disgression caused by love of westernÂ  culture in Japanese colonialization